2003
DOI: 10.1128/jcm.41.2.667-670.2003
|View full text |Cite
|
Sign up to set email alerts
|

Six Rapid Tests for Direct Detection of Clostridium difficile and Its Toxins in Fecal Samples Compared with the Fibroblast Cytotoxicity Assay

Abstract: .7% of all samples tested, and no significant differences in sensitivity or specificity were noted between HSCT and non-HSCT patients. IAs, while not as sensitive as direct fecal CBA, produce reasonable predictive values, especially when both antigen and toxin are detected. They also offer significant advantages over CBA in terms of turnaround time and ease of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 32 publications
(20 reference statements)
5
46
0
4
Order By: Relevance
“…They showed that another widely used EIA, the C. difficile Tox A/B II assay (TechLab, Blacksburg, VA), which has performance characteristics similar to those of the A/B EIA (11,12,19), had a sensitivity of only 36% for C. difficile detection when the results were compared to those obtained by the use of a two-step algorithm in which specimens were first tested for the presence of the glutamate dehydrogenase (GDH) antigen by a solid-phase EIA (C. Diff Chek-60; TechLab) and the positive results were confirmed by the CTN assay. The test for the GDH antigen proved to be an excellent screening test, with a sensitivity of Ͼ95% and a negative predictive value of Ͼ99% compared with the results of the CTN assay (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that another widely used EIA, the C. difficile Tox A/B II assay (TechLab, Blacksburg, VA), which has performance characteristics similar to those of the A/B EIA (11,12,19), had a sensitivity of only 36% for C. difficile detection when the results were compared to those obtained by the use of a two-step algorithm in which specimens were first tested for the presence of the glutamate dehydrogenase (GDH) antigen by a solid-phase EIA (C. Diff Chek-60; TechLab) and the positive results were confirmed by the CTN assay. The test for the GDH antigen proved to be an excellent screening test, with a sensitivity of Ͼ95% and a negative predictive value of Ͼ99% compared with the results of the CTN assay (18).…”
mentioning
confidence: 99%
“…The latter is the most widely used test for the detection of C. difficile toxins in the United States (4). Recent studies (11,20) have shown that this assay has both excellent sensitivity (Ͼ90%) and excellent specificity (Ͼ95%) compared to the results of a tissue culture cytotoxicity neutralization (CTN) assay, an assay frequently considered the "gold standard" for the diagnosis of C. difficile disease (1,9,11,12,15,18,19,21). Other data suggest that the detection of toxigenic strains of C. difficile is actually a more sensitive approach to the diagnosis of C. difficile disease (5,6,13,14), but culture is infrequently done for diagnostic purposes in the United States because of its slow turnaround time and the need for special isolation media and technical expertise.…”
mentioning
confidence: 99%
“…Fecal toxin assay by cell cytotoxicity neutralization assay (CCNA) is still regarded as the gold standard. CCNA is more sensitive than toxin detection by immunoassays but has a turnaround time of up to 3 days, is labor-intensive, and requires facilities for cell culture (3,10,11). Toxin enzyme immunoassays are more rapid and easier to perform but are suboptimal if used as stand-alone assays due to the low sensitivity compared to CCNA or toxigenic C. difficile culture (3,7,10).…”
mentioning
confidence: 99%
“…Primero, su ubicación en un solo centro de atención que, además, es un hospital universitario, no permite la generalización de los resultados. Segundo, a pesar de contar con una prueba inmunológica de alto rendimiento para la detección de la toxina, de sensibilidad cercana al 80 % (38), el método utilizado no es el más sensible, lo cual no permite descartar con certeza que algunos de los controles correspondieran realmente a casos. Pese a ello, los métodos diagnósticos empleados en el mundo (9) y en Latinoamérica (21) están restringidos, en general, a la detección de toxinas y son principalmente ensayos enzimáticos (toxinas A o AB); en pocas ocasiones se recurre a métodos de cultivo celular para determinar los cambios citopáticos (39,40) o a pruebas de reacción en cadena de la polimerasa.…”
Section: Discussionunclassified